The treatment of families in the Australian welfare state, 1984 to 20101. Issue 2 (July 2014) - Tapper, Alan; Fenna, Alan; Phillimore, John
Abstract : This paper uses Australian Bureau of Statistics' fiscal incidence figures to track trends in the treatment of families with children in the Australian welfare state across the period 1984 to 2010. Our four main findings are that: sole parent families gained while couple families made no net gain; there was no growth in 'middle class welfare'; couple families are slightly better off than elderly households in terms of their final incomes, but considerably less well off in terms of their net worth; and stated differences in policy intentions by the major political parties have had little influence on trends in actual government redistribution.